Philosophical and pedagogical views of T. I. Filippov - L. E. Shaposhnikov (Вестник Мининского университета, 2021)
Introduction. The paper analyses the ideas of T.I. Fillipov, a representative of the Slavophil school of thought. Fillipov’s commitment to the Slavophil doctrine formed the distinctive features of his philosophical and pedagogical beliefs. The present paper is aimed at examining these features and revealing Fillipov’s role in the cultural and educational development of Russia.Materials and Methods. The original works by T. I. Fillipov serve as the material of the present study. For achieving the research goal, a number of traditional methods were used: analysis, interpretation, generalization, description, the comparative method. Besides, the historico-logical method proved to be particularly important for embracing the meaning of Filllipov’s activity to the Russian philosophy and enlightenment.Results. The key ideas of T. I. Fillipov were identified. In the field of religion the scholar proposed to renovate the principles of sobornost as a means to overcome the faith crisis. He was also a proponent of the traditional values in education and culture. To preserve these, T. I. Fillipov suggested to enhance the national orientation in education and undertake measures to safeguard the folk culture. The present paper also makes a special emphasis on the scholar’s attention to the still relevant problem of the relationship between Russia and the Slavophilism. Discussion and Conclusion. The contribution made by T. I. Fillipov to the Russian philosophy and pedagogy is acknowledged. The scholar’s ideas concerning the unique role of the orthodox Christianity, Russia’s mission in the world history, the value of the country’s folk culture   remain acute today. T. I. Fillipov’s belief in the pedagogical value of the humanitarian disciplines shaping citizens’ patriotism is also very up to date. It is evident that Fillipov’s works – both published and archives - are worth further studying.